2017
DOI: 10.1371/journal.pone.0174071
|View full text |Cite
|
Sign up to set email alerts
|

TASK-1 potassium channel is not critically involved in mediating hypoxic pulmonary vasoconstriction of murine intra-pulmonary arteries

Abstract: The two-pore domain potassium channel KCNK3 (TASK-1) is expressed in rat and human pulmonary artery smooth muscle cells. There, it is associated with hypoxia-induced signalling, and its dysfunction is linked to pathogenesis of human pulmonary hypertension. We here aimed to determine its role in hypoxic pulmonary vasoconstriction (HPV) in the mouse, and hence the suitability of this model for further mechanistic investigations, using appropriate inhibitors and TASK-1 knockout (KO) mice. RT-PCR revealed expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 41 publications
5
15
1
1
Order By: Relevance
“…However, a functional role of TASK-1 channels in pulmonary arteries of mice was not observed (Manoury, Lamalle, Oliveira, Reid, & Gurney, 2011;Murtaza et al, 2017). We also did not observe consid- (Mulvany, Nilsson, & Flatman, 1982;Neild & Kotecha, 1987).…”
Section: Task-1 Channels Are Important For the Regulation Of Membracontrasting
confidence: 60%
“…However, a functional role of TASK-1 channels in pulmonary arteries of mice was not observed (Manoury, Lamalle, Oliveira, Reid, & Gurney, 2011;Murtaza et al, 2017). We also did not observe consid- (Mulvany, Nilsson, & Flatman, 1982;Neild & Kotecha, 1987).…”
Section: Task-1 Channels Are Important For the Regulation Of Membracontrasting
confidence: 60%
“…AEA and NAGly have been demonstrated to possess potential vasodilatory properties, as has AEA in hPAs and rPAs [ 10 ] and NAGly in the systemic arterial bed [ 43 ]. So far, only AEA has been shown to reduce hypoxia-induced vasoconstriction (an important feature of PH), although it failed to modify the vascular caliber under normoxia in murine intra-acinar and pre-acinar arteries [ 44 ]. Metabolites of AEA have been demonstrated to mediate hypoxia-induced PH in mice [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“… showed that the guanylate cyclase activator, riociguat, a novel treatment for pulmonary hypertension, enhances current through TASK‐1 channels but does not recover current through mutant TASK‐1 channels, seen in pulmonary hypertension patients. While there is compelling evidence that KCNK3 is involved in the pathogenesis of pulmonary hypertension in humans , KCNK3 does not play a key role in initiating HPV of mice pulmonary hypertension , but it may participate in its maintenance . However, KCNK3 /TASK‐1 channel did not form a functional channel in mice which is not a suitable model to study KCNK3 in PA hypertension .…”
Section: Pathophysiological Roles Of Potassium Channelsmentioning
confidence: 98%